OSGi and Apache Felix 3.0 : beginner's guide : build your very own OSGi applications using the flexible and powerful Felix framework /: beginner's guide : build your very own OSGi applications using the flexible and powerful Felix framework. (2010) - Gédéon, Walid
No abstract available